Formulation and Evaluation of Sustained release tablets of Venlafaxine HCl - Fazli, Abdul Aala; Wani, Taha Umair; Raza, Syed Naiem; Mir, Khalid Bashir; Khan, Nisar Ahmad (Journal of Drug Delivery and Therapeutics, 2019)
The aim of the present study was to develop a tablet formulation for sustained release of venlafaxine HCl. Control or sustained release formulations have great applications in improving the physicochemical properties and the pharmacokinetic profile of the drugs. Carbopol tablets containing venlafaxine HCl were developed successfully by wet granulation technique. The tablets were evaluated for matrix integrity and drug release in 0.1 N HCl using USP II dissolution apparatus maintained at optimum conditions. The developed tablets were robust and possessed excellent physicochemical properties. The tablets showed great matrix integrity and withstood the hydrodynamic environment of the dissolution medium for > 12 hours. The hydration and swelling behaviour of the tablets was excellent. It was found that the swelling characteristics of the tablets depended on the amount of the polymer used in the tablets as well as the polymer/drug ratio. The tablets provided more than 90% drug release over a period of 12 hours. The drug release data was subjected to kinetic dissolution modelling. It was found that the drug release from the tablets followed Korsmeyer-Peppas model of drug release. This suggests that the mechanism of the drug release from the formulations may be both diffusion as well as polymer erosion.Keywords: Sustained release, Carbopol, Venlafaxine HCl